(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talked about the use of new, modern multimedia tools and the participation of teachers in learning foreign languages, mainly in the environment where the French language is taught.